Disparities in mortality among acute myeloid leukemia‐related hospitalizations. (4th August 2022) - Alam, Sara Taveras; Dongarwar, Deepa; Lopez, Elyse; Yellapragada, Sarvari; Rivero, Gustavo; Huang, Quillan; Miler‐Chism, Courtney; Mims, Martha; Salihu, Hamisu M.
Abstract: Racial and socioeconomic disparities have become apparent in acute myeloid leukemia (AML) outcomes. We conducted a retrospective cohort study of hospitalizations for adults with a diagnosis of AML from 2009 to 2018 in the Nationwide Inpatient Sample (NIS). We categorized patients' ages in groups of <60 years and ≥60 years and stratified them by reported race/ethnicity. Exposures of interest were patient sociodemographics, hospital characteristics, and Elixhauser‐comorbidity Index. Outcome of interest was in‐hospital death. Statistical analyses included survey logistic regression to generate adjusted odds ratios (aORs) and 95% confidence intervals (CIs) to quantify the independent associations between patient characteristics and mortality. Of 622, 417 AML‐related hospitalizations, 57.6% were in patients ≥60 years. The overall rate of in‐hospital death was 9.4%. Compared to patients <60, older patients experienced a higher rate of in‐hospital death. In both age groups and in all ethnicities, mortality decreased over time. Differences in mortality were observed based on gender, payer, hospital location, and teaching status. For hospitalizations in patients ≥60, NH‐Black race was associated with inferior in‐hospital death outcomes (OR 1.17; CI 1.08–1.28). Urban teaching hospitals were associated with a 38% increase (OR 1.38; CI 1.06–1.80) in inpatient mortality in patients <60 and a 15% decrease (OR 0.85; CI 0.77–0.95) in inpatient mortality in patients ≥60. Our results highlight the increased need to recognize the role of race/ethnicity and socioeconomic factors and their contribution to disparate outcomes in AML. Abstract : We evaluated sociodemographic disparities in the mortality of hospitalized patients with acute myeloid leukemia (AML) through a retrospective cohort study of hospitalizations for adults with a diagnosis of AML from 2009 to 2018 in the United States using the Nationwide Inpatient Sample (NIS). Race, gender, and teaching hospital status were found to be associated with disparate outcomes, in addition to established differences in mortality based on age. Our results highlight the increased need to recognize the role of race/ethnicity and socioeconomic factors and their contribution to outcomes in AML.